Kings of disaster: dualism, centralism and the scapegoat king in Southeastern Sudan - Simonse, Simon (Studies in human society, 1992)
Review: Simon Simonse is the first field archeologist of whom I know to draw upon Girard's mimetic theory, especially for the light it sheds on consensual scapegoating. Simonse shows that one explanatory model can accommodate both political and sacral aspects of kingship, for the two are actually inseparable in the cases studied. He likewise demonstrates that the conventional distinction between state and stateless societies does not hold up, and that the only difference between centralized and segmentary political systems lies in the relative emphasis placed on the role of the king as contrasted to that of enemy victims. His conclusions are reached on the basis of a five year study of five communities on the east bank of the Nile River. Of particular interest for me was Simonse's graphic description of simulated and actual regicide. He identifies the simulation of regicide as a ritual drama (pp. 354-59). Ordinarily some sort of free that is vut and burnt or leaves that are pounded serve as a substitute for the monarch (cf. Exodus 15:24). In the ensuing discussion he documents 24 cases of actual regicide ocurring between 1850 and 1984 (pp. 359-73). He holds that the actual instances of killing the monarch are neither ritual nor political assassination. Regicide is, rather, a deliberate act, "the tragic dénouement of a protracted confrontation [of the community] with its king" (p. 372). This observation is related to one of Simonse's criticisms of Girard, namely that the scapegoating mechanism does not always work to suppress or mystify violence. Concerning Simonse's denial that regicide is a ritual act, the full scope of his analysis certainly indicates that it is closely related to ritual in that it is an organized activity generated by the deep structure of the cultural tradition. The main object of the scapegoat mechanism is the person of the monarch; if the rains do not come, it is he or she who must bear the blame. The instance Simonse reports in detail, the lynching of the queen of the Pari, has many features of ritual procedure. She was surrounded by the male warriors of the ruling generation, beaten and passed through a fire, and, most significantly, her abdomen was cut open and a melon crushed and mixed with her stomach contents and blood. The mixture was placed back in her stomach, her mouth was pierced with thorns, and her body was left in the bush. Before reentering their village the lynchers "slaughtered a goat and took out its stomach contents. These were smeared onto their bodies together with a mixture of ant-hill soil, water, and wild cucumber" (p. 370). Simonse's research leads him to three critical modifications of Girard's theory: (1) There is more of a reciprocal tension between king and subjects than described by Girard; the king is a victimizer and political entrepreneur as well as a victim in specific circumstances (above all, lack of rain). (2) If the death of the king is violent, it is feared that the hoped for transformation, the releasing of the rains, may not occur. (3) Closely related to the second criticism, the scapegoating as such is not ignored or mystified, for the violence of regicide does not allow the community to "reap the fruits of kingship in good conscience" (p. 423). I think a multitude of areas of research are now opening up in which the mimetic theory may be modified, expanded, refined. The work of a social scientist like Simonse who combines so ably a grasp of the mimetic theory and extensive empirical research should command our respect. I would note briefly that all three of Simonse's critical rejoinders to Girard do not seem, to me at least, like real challenges to the model. The first point about the actual power of the monarch, even in his/her victim status, is covered in principle in Girard's Things Hidden, pp.51-57. As for points two and three, which I think finally amount to one criticism, it is quite common for traditional, nonwriting peoples to be concerned about violence and to rid themselves of its pollution once they have been contaminated. For Simonse to make his case he must deal more definitely with the following questions. Is it the case that these Nilotic peoples believe it is bad to kill the monarch because it is wrong to murder someone - or do they believe it is too bad because violence is involved? And do they know they are converging upon a victim whose status is central to the logic of the system, which itself began arbitrarily through violence - or do they think that there is something sacrally grounded and ultimately meaningful in this act? And finally, are they aware of transferring their own mimetic conflicts onto the leader/rainmaker - or do they understand the looming drought and all their other troubles as stemming from the one they kill? Simonse's point would hold if he could say yes to the first alternative in each question. [Author: Williams, James G. In: COV&R: Bulletin of the Colloquium on Violence and Religion no. 6 (March 1994): 9f.]